2019
DOI: 10.15414/jmbfs.2019.8.4.1026-1034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heavy Metals and Pesticides Contents in Market-Gardening Products Sold in Some Principal Markets of Ouagadougou (Burkina Faso)

Abstract: Pesticides and heavy metals are persistent organic pollutants responsible for immune deficiency, certain types of cancer, and decreased length of pregnancy.In this study, 20 chemical pesticides and 4 heavy metals were detected from 120 samples of 4 types of vegetables and 40 samples of babenda collected from Ouagadougou principal markets. The "babenda" is a Burkinabe dish made mainly of leafy vegetables (Hibiscus sabdariffa, Amaranthus hybridus, and Cleome gynandra) coarsely chopped and millet or rice that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…This situation results from the inappropriate or abusive use of pesticides and from the lack of environmental education for farmers (Licciardi et al, 2007). However, our results are in contrast to those of Son et al (2017) and Tarnagda et al (2019) who reported respectively that pyrethroid and organochlorines are the predominant families. Those differences could be explained by the diversity of pesticides used depending on the crop areas.…”
Section: Discussioncontrasting
confidence: 89%
“…This situation results from the inappropriate or abusive use of pesticides and from the lack of environmental education for farmers (Licciardi et al, 2007). However, our results are in contrast to those of Son et al (2017) and Tarnagda et al (2019) who reported respectively that pyrethroid and organochlorines are the predominant families. Those differences could be explained by the diversity of pesticides used depending on the crop areas.…”
Section: Discussioncontrasting
confidence: 89%
“…This may be due to the misuse of pesticides and the lack of environmental education of farmers; these powders cannot be directly used. Any use of raw material with pesticide contents above the limit requires prior treatment (bark washing, powder decoction), as heat and washing reduce the concentration of pesticides [24].…”
Section: Resultsmentioning
confidence: 99%
“…Zinc is required to develop even functions and express genes in our bodies in addition to helping in the synthesis of different proteins and healing of wounds. [15][16][17] Our study suggests the zinc concentration in Methi leaves is the highest while it is the lowest in Drumstick leaves, so the leaves are listed in the following order: Methi leaves > Lal Bhaji > Drumstick leaves. The zinc is present in this kind of leaves is extremely low.…”
Section: Table 2 Concentration Of Metal In Different Leafy Vegetables...mentioning
confidence: 86%